Novel one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in water - Palimkar, Sanjay S.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Green Chemistry, 2007)
A novel green and efficient one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in excellent isolated yields has been reported. The methodology initially involves the formation of ynones via coupling of a wide range of acid chlorides with terminal alkynes catalysed by Pd(OAc)(2) under copper-, ligand- and solvent-free conditions in just 10 min at rt followed by the Michael addition and cyclocondensation of o-phenylenediamines added in situ using water as a solvent at reflux temprature. In addition, the structure of the benzodiazepine was confirmed to be the diimino molecule and not the enamine by X-ray crystallographic analysis of the benzodiazepine 4b. The methodology is suitable for the operation in combi-chem mode to generate libraries of a diverse array of benzodiazepines. The methodology has been successful in achieving the twin green chemistry objectives of a solvent and ligand free operation and the use of water as a non-hazardous, inexpensive and readily available solvent in the sequential reaction steps performed in situ, thus combining the features of both economic and environmental advantages.